1999
DOI: 10.1002/(sici)1521-3765(19990401)5:4<1202::aid-chem1202>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Gd(DTPA-bisamide)alkyl Copolymers: A Hint for the Formation of MRI Contrast Agents with Very High Relaxivity

Abstract: A variable-temperature, multiple-field 17 O NMR and EPR spectroscopic study has been performed on three Gd(DTPA-bisamide)alkyl copolymers, [Gd(DTPAÀBA)À(CH 2 ) n ] x (n 6, 10,12;N,N',N'',. The rate and mechanism of water exchange is identical for the polymer complexes and [Gd(DTPAÀBMA)(H 2 O)], which can be considered as the monomer unit of the polymers. Transverse electronic relaxation rates, measured by EPR, increase with increasing rotational correlation time. Rigid intramolecular micellelike structures for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
69
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 25 publications
(50 reference statements)
1
69
0
1
Order By: Relevance
“…SEC chromatograms of the polymers DTPA-HMD and DTPA-CHD, and of the respective Gd 3+ complexes. 4) are comparable to those reported by Toth et al (27) (from this publication, a τ M value of 1.03 ms can be calculated at 310 K for the compound with n ) 6). The observed constancy of τ M is in line with the general observation that derivatization has hardly any effect on the water exchange rate of bisamides, which limit the relaxivity values.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…SEC chromatograms of the polymers DTPA-HMD and DTPA-CHD, and of the respective Gd 3+ complexes. 4) are comparable to those reported by Toth et al (27) (from this publication, a τ M value of 1.03 ms can be calculated at 310 K for the compound with n ) 6). The observed constancy of τ M is in line with the general observation that derivatization has hardly any effect on the water exchange rate of bisamides, which limit the relaxivity values.…”
Section: Resultssupporting
confidence: 90%
“…Other studies with this type of DTPA copolymers, containing as linking units long hydrophilic poly(ethyleneglycol) (PEG) (40), or hydrophobic alkyl chains with a varying number (n) of methylenes (29), showed that higher relaxivities were obtained only for long hydrophobic chains with n g 10. For these polymers, hydrophobic interactions between different chains lead to intramolecular aggregates and the formation of more rigid compact, globular structures, with slower local motions and global rotation, leading to higher relaxivity (27,29). Studies with other polymeric carriers (15,16) have also shown that higher relaxivities are obtained for more rigid compact, globular structures, for example by increasing the degree of substitution of the carrier.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter parameter influences significantly the relaxivity profile in the Larmor frequency range 10-100 MHz. Theoretically, the relaxivity versus frequency curve should present a peak of relaxivity, whose theoretical value should culminate at approximately 100-200 mM −1 s −1 for large Gd-containing particles [4].…”
Section: Introductionmentioning
confidence: 99%
“…Efforts are thus devoted to optimise the water residence time, s M , and therefore to alleviate the limitation of the complex's relaxivity. Amide linkages have to be avoided since they are known to prolong the water residence time [6][7][8][9][10][11][12][13][14]. On the contrary, a C4-substitution of the ethylenic bridge of DTPA by an ethoxybenzyl group, a benzyl, or a MAGMA (2004) 16: 235-245 Abstract Among other factors influencing the residence time of the coordinated water (s M…”
mentioning
confidence: 99%